Functional evaluation in inherited retinal disease. Issue 11 (25th November 2021) - Daich Varela, Malena; Georgiou, Michalis; Hashem, Shaima A; Weleber, Richard G; Michaelides, Michel
Abstract : Functional assessments are a fundamental part of the clinical evaluation of patients with inherited retinal diseases (IRDs). Their importance and impact have become increasingly notable, given the significant breadth and number of clinical trials and studies investigating multiple avenues of intervention across a wide range of IRDs, including gene, pharmacological and cellular therapies. Moreover, the fact that many clinical trials are reporting improvements in vision, rather than the previously anticipated structural stability/slowing of degeneration, makes functional evaluation of primary relevance. In this review, we will describe a range of methods employed to characterise retinal function and functional vision, beginning with tests variably included in the clinic, such as visual acuity, electrophysiological assessment and colour discrimination, and then discussing assessments often reserved for clinical trials/research studies such as photoaversion testing, full-field static perimetry and microperimetry, and vision-guided mobility testing; addressing perimetry in greatest detail, given it is commonly a primary outcome metric. We will focus on how these tests can help diagnose and monitor particular genotypes, also noting their limitations/challenges and exploring analytical methodologies for better exploiting functional measurements, as well as how they facilitate patient inclusion and stratification in clinical trials and serve as outcome measures.